Foundation Species Abundance Influences Food Web Topology on Glass Sponge Reefs - Archer, Stephanie K.; Kahn, Amanda S.; Thiess, Mary; Law, Lauren; Leys, Sally P.; Johannessen, Sophia C.; Layman, Craig A.; Burke, Lily; Dunham, Anya (Frontiers in Marine Science, 2020)
Foundation species support communities across a wide range of ecosystems. Non-trophic interactions are considered the primary way foundation species influence communities, with their trophic interactions having little impact on community structure. Here we assess the relative trophic importance of a foundation species and assess how its abundance can influence food web topology. Using empirical data and published trophic interactions we built food web models for 20 glass sponge reefs to examine how average live reef-building sponge abundance (proxied by percent cover) at the reef level is correlated with community structure and food web network topology. Then, using a generalized food web model and stable isotope data we examined the relative importance of sponges. Sponges were consumed by all species examined and contributed significantly to their diets. Additionally, sponges were the second most important node in our generalized reef food web. Several metrics of food web topology (connectance, clustering, and median degree) and community structure exhibited a threshold response to reef-building sponge cover, with the change point occurring between 8 and 13% live sponge cover. Below this threshold, as average sponge cover increases, the consumers observed on a reef rely on fewer sources and are consumed by fewer predators, resulting in food webs that are more clustered and less connected. Above the threshold, as average sponge cover increases, the reefs’ food webs are less clustered and more connected, with consumers utilizing more sources and having more predators. This corresponds with the finding that several generalist predators (e.g., rockfishes) are associated with high sponge cover reefs. Our results are not consistent with previous reports that increasing foundation species abundance decreases connectance in food webs. We propose that the influence of foundation species on food web topology may be dependent on palatability, and therefore relative trophic importance, of the foundation species. Finally, our findings have important implications for sponge reef conservation and management, as they suggest that reefs below the 10% sponge cover threshold support different communities than high live sponge cover reefs.